The Importance of Applying Parenting Education Program for The Student’s Parent in Elementary School - Anggit Putri Natasa; Rahma Arifah Ludfiani; Moh Salimi (Universitas Sebelas Maret, 2019)
Parents are the child's first mentors in the learning process at home. Some parents feel unable to guide children at home. Parenting Education Program (PEP) has the opportunity as a solution to help parents guide their children at home. This study focuses on the definition, application, benefits and importance of Parenting Education Programs. The results of this study include: (1) PEP is a training program held by schools to provide guidance in the form of knowledge and skills to parents; (2) The application of PEP has been applied in several elementary schools, namely SDIT Ar Raihan Bantul, SD Surya Buana Malang and SD Insan Teratai Tangerang; (3) The benefits of PEP are establishing a good relationship between school and parents, increasing parental knowledge and increasing parental confidence; (4) PES is important to be implemented in many elementary schools that do not directly involve parents in children's education